Thermometry: A simple objective method for burn depth assessment - Pawan Agarwal; Dhananjaya Sharma; Sudesh Wankhede; Lokesh Kumar Patel (Wolters Kluwer Medknow Publications, 2018)
Introduction: Accurate assessment of burn wound depth is important because it determines the choice of treatment and prognosis. Clinical evaluation remains the most commonly used modality with its accuracy varies from 50% to 70%. This study was conducted to assess the accuracy and feasibility of burn wound depth using noninvasive noncontact technique using infrared thermometry. Materials and Methods: Fifteen patients' burn wounds depth was classified clinically into full-thickness, deep partial-thickness, or superficial partial-thickness burns. Thermometry was performed on 3rd day of burn injury using the handheld infrared thermometer. A punch biopsy was taken from all three areas (deep, deep-partial, and superficial-partial burns). A correlation between surface temperature and depth of burn by histopathology was done. Results: 12/15 patients total burn surface area (TBSA < 65%) survived and three patients (TBSA > 65%) died. In 11/12survivors, thermometry correctly predicted final burn depth. One of 12 burns superficial burn was wrongly assessed clinically as full thickness but was correctly classified by thermometry and healed within 21 days without surgery. 3/12 burns on clinical assessment thought to be superficial were deep; two were correctly predicted by thermometry. Conclusions: Handheld infrared thermometer can be used in conjunction with clinical examination to improve the efficacy of burn wound depth assessment.